Temporal Contextual Logic Programming - Nogueira, Vitor (2009)
The importance of temporal representation and reasoning is well known not only in the database community but also in the artiﬁcial intelligence one. Contextual Logic Programming (CxLP) is a simple and powerful language that extends logic programming with mechanisms for modularisation. Recent work not only presented a revised speciﬁcation of CxLP together with a new implementation for it but also explained how this language could be seen as a shift into the Object-Oriented Programming paradigm. In this paper we propose a temporal extension of such language called Temporal Contextual Logic Programming. Such extension follows a reiﬁed approach to the temporal qualiﬁcation, that besides the acknowledge increased expressiveness of reiﬁcation allows us to capture the notion of time of the context. Together with the syntax of this language we also present its operational semantics and an application to the management of workﬂows.